Role of Vigilin and RACK1 in dengue virus-Aedes aegypti-Wolbachia interactions - Guijie Wang; Mazhar Hussain; Zhi Qi; Sassan Asgari (mSphere)
ABSTRACT Vigilin is a large and evolutionary conserved RNA-binding protein (RBP), which can interact with RNA through its KH domain. Vigilin is, therefore, a multifunctional protein reported to be associated with RNA transport and metabolism, sterol metabolism, chromosome segregation, carcinogenesis, and heterochromatin-mediated gene silencing. The receptor for activated C kinase 1 (RACK1) is another highly conserved protein involved in many cellular pathways. Functional studies in human cells indicated that RACK1 interacts with Vigilin to promote dengue virus (DENV) replication. Both proteins are associated with the endoplasmic reticulum. Here, we investigated the significance of Vigilin and RACK1 homologs in Aedes aegypti mosquitoes concerning DENV replication and Wolbachia infection. We identified the homologs of the two genes in Ae. aegypti (AeVigilin and AeRACK1), which were upregulated in DENV-infected Aag2 cells and mosquitoes, and silencing them in Aag2 cells resulted in reduced DENV replication. Co-immunoprecipitation showed that AeRACK1 and AeVigilin interact in mosquito cells. Interestingly, we also found upregulation of both genes in a Wolbachia-infected cell line (Aag2.wAlbB). Furthermore, silencing AeVigilin and AeRACK1 in Aag2.wAlbB cells reduced DENV replication but increased Wolbachia density. However, we did not find a significant effect on DENV replication after silencing both genes in Ae. aegypti mosquitoes. Overall, our results support the involvement and significance of AeVigilin and AeRACK1 in DENV replication in Ae. aegypti.IMPORTANCEDengue virus (DENV), transmitted mainly by Aedes aegypti mosquitoes, poses significant health risks. Identifying factors involved in the virus replication in mosquitoes and human hosts is essential for devising control measures. In this study, we show that Vigilin and the receptor for activated C kinase 1 (RACK1), two proteins shown to play a role in the replication of DENV in human cells, are induced in mosquitoes and cell lines following DENV replication. Both proteins reside in the cytoplasm, where they interact similarly to human cells. Silencing the genes in mosquito cells significantly reduced virus replication. Furthermore, we found that both genes are induced in mosquito cells transinfected with Wolbachia, a bacterium that blocks DENV replication. The results help better understand the role of the common factors supporting DENV replication in mosquitoes and human cells.